2020
DOI: 10.1002/solr.201900463
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Importance of Precursor Preparation for Highly Efficient and Stable Phenethylammonium‐Based Perovskite Solar Cells

Abstract: For the fabrication of low‐dimensional perovskite solar cells, understanding the effect of precursor preparation on film formation is critical to achieve high‐quality perovskite film and, therefore, high efficiency in related solar devices. Herein, the two methods to prepare phenethylammonium‐based mixed perovskite precursors with the same chemical composition are reported. These methods are called 1) different phase (DP) and 2) same phase (SP) methods as the former involves the mixing of a 3D perovskite precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Another method called the same phase method achieved decent stability under a high humidity environment by f a b r i c a t i n g q u a s i -2 D P E A 2 F A n − 1 P b n I 3 n + 1 a n d PEA 2 MA n−1 Pb n Br 3n+1 separately and then mixing them together into perovskite. 117 The reason for the high stability is that there is no formation of a different phase when the hydrophobic phenethylammonium (PEA) is incorporated into the perovskite, fostering a uniform perovskite film. The other method named self-seeding growth was developed to bolster a longer time moisture stability of PSCs (Figure 5c).…”
Section: Process Engineeringmentioning
confidence: 99%
See 3 more Smart Citations
“…Another method called the same phase method achieved decent stability under a high humidity environment by f a b r i c a t i n g q u a s i -2 D P E A 2 F A n − 1 P b n I 3 n + 1 a n d PEA 2 MA n−1 Pb n Br 3n+1 separately and then mixing them together into perovskite. 117 The reason for the high stability is that there is no formation of a different phase when the hydrophobic phenethylammonium (PEA) is incorporated into the perovskite, fostering a uniform perovskite film. The other method named self-seeding growth was developed to bolster a longer time moisture stability of PSCs (Figure 5c).…”
Section: Process Engineeringmentioning
confidence: 99%
“…Adopting appropriate solution-based methods to reduce the defects and improve perovskite film quality (Figure a) fosters better moisture and oxygen stability. It was reported that 93% retention of original PCE of 20.63% was realized under 40% humidity after 500 h for PSC fabricated by a dropwise addition method, which included two steps: the PbI 2 film was first deposited and then the FA/MA iodide with isopropanol (IPA) and dimethyl sulfoxide (DMSO) was introduced dropwise (Figure b) . Carefully controlling the dropwise addition process resulted in highly compact and flat surface and larger crystal size with well-packed crystals, substantially mitigating GBs and defect states, increasing light absorption, and inhibiting carrier recombination.…”
Section: Process Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the introduction of large cations, there is a heterogeneous distribution of various n phases in 2D perovskite (Figure 3c), [108] ITO/SnO 2 /PVK/Spiro-OMeTAD/Ag (TMA) 2 FA 4 Pb 5 I 16 1.15 79 22.15 20.12 2021 [109] (ITO)/NiOx/PVK/PCBM (50 wt% ICBA)/BCP/Ag BA 2 MA 2 Pb 3 I 10 1.23 72.17 13.61 12.07 2018 [67] ITO/Cu:NiOx/PVK/PCBM/BCP/Ag (TEA) 2 (MA) 2 Pb 3 I 10 1.23 75.3 15.85 14.68 2020 [110] ITO/PEDOT:PSS/PVK/PCBM/BCP/Ag BA 2 MA 4 Pb 5 I 16 1.1 77 16.74 14.09 2019 [111] ITO/PEDOT:PSS/PVK/PCBM/BCP/Ag (ThMA) 2 (FA) holes can spontaneously transfer from the high n phase to the low n phase in the gradient phase distribution, and the electrons move in the opposite direction, as shown in Figure 3b. [30] Significant directional changes in mobility and conductivity are seen in 2D perovskite; these differences are more pronounced in the direction of the inorganic plate than in the perpendicular to the inorganic plate.…”
Section: Carrier Transportmentioning
confidence: 99%